(untitled) (Journal of Tikapur Multiple Campus, 2022)
Rice crop plays a key role to maintain the food security in Nepal. However, inadequate knowledge on the economics of production hampers the level of production. Thus, this study seeks to analyze the profitability, resource use efficiency, and constraints faced in rice seed production in Kailali, Nepal. 158 households were selected using a simple random sampling technique. The primary data were collected from September to November 2021. The descriptive statistics, Benefit-Cost ratio, Cobb-Douglas production function, and scaling techniques were applied for data analysis using SPSS. Further, gross return NRs.115, 772/ha and benefit-cost ratio1.70 indicated that rice seed production was profitable with the productivity of 3.81 mt/ha. Estimation of resource use efficiency showed that the investment in seed and fertilizer needs to be increased by 53% and 63% respectively. The cost of tillage operations, labour, and agrochemicals should be decreased. The scaling technique resulted that pest in storage, inadequate capital and insufficient training were the major constraints. It is concluded that rice seed production is profitable with better yield, but the necessity was observed for the optimal allocation of inputs. The training, better storage facilities and credit access would be helpful to increase the income of farmers.